Terapia ocupacional educacional: revendo o desenvolvimento infantil por meio da teoria histórico-cultural - Ribeiro, Mara Alice [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research was developed in the Line Childhood and Education, from Education Post- Graduate Program at FCT - UNESP - Presidente Prudente. It aims to characterize the development of babies and young children who attended in 2012 some public-municipal nurseries in a city in northwestern São Paulo. The data collection instrument was the Table for Observation of the Child Development (TODI) that the Occupational Therapists of the city's Education Department, used in 2012 to identify the child development of children aged four months to two years and five months. The search target audience was 218 children enrolled in 12 of these nurseries and to achieve the goal, the data from TODIs were described and analyzed; through bibliographic and documentary research procedures were correlated through quantitative and qualitative analyzes, with the development process of the subjects, featuring child development as a historical-cultural process. The theoretical and methodological assumptions that underlie this process were the cultural-historical theory and the historical and dialectical materialism. The results of this study showed that in almost all of the children evaluated, their development was age-appropriate. Furthermore, it was found that the characteristic development, through its variable developmental delay, suffered interference of the gender and region characteristics, showing probably that, the concrete conditions of life and education interfere in the human development...

Esta pesquisa, desenvolvida junto à linha Infância e Educação do Programa de Pós-Graduação em Educação da FCT - UNESP - Presidente Prudente teve como objetivo caracterizar o desenvolvimento de bebês e crianças pequenas que frequentaram em 2012 alguns berçários público-municipais de uma cidade do noroeste paulista. O instrumento de coleta de dados foi a Tabela para Observação do Desenvolvimento Infantil (TODI), que as Terapeutas Ocupacionais da Secretaria de Educação da cidade, utilizaram no ano de 2012 para identificar o desenvolvimento infantil de crianças na faixa etária de quatro meses a dois anos e cinco meses. O público-alvo da pesquisa constituiu-se de 218 crianças matriculadas em 12 berçários e para atingir o objetivo, os dados das TODIs foram descritos e analisados; através de procedimentos de pesquisa bibliográfica e documental, foram correlacionados por meio de análises quantitativas e qualitativas ao processo de desenvolvimento dos indivíduos, caracterizando seu desenvolvimento como um processo histórico-cultural. Os pressupostos teóricos e metodológicos que fundamentaram este processo partiram da Teoria históricocultural e do materialismo histórico e dialético. Os resultados deste estudo mostraram que, na grande maioria das crianças avaliadas naquele ano o desenvolvimento estava adequado à idade. Por outro lado, verificou-se que a característica desenvolvimento, por meio de sua variável atraso no desenvolvimento, sofreu interferências relacionadas ao gênero e região, demonstrando no último caso que provavelmente, as condições objetivas de vida e educação interferem no processo de desenvolvimento humano...
Keywords: Educação; Terapia ocupacional; Crianças - Desenvolvimento; Cultura; Education